Case of endobronchial metastasis from breast cancer accompanied with Cunninghamella bertholletiae tracheobronchial mycetoma. Issue 12 (December 2019) - Uno, Kenji; Hishiya, Naokuni; Matsuda, Masayuki; Kai, Yoshiro; Amano, Masayuki; Nakamura, Atsuhiro; Tohjyo, Takashi; Kawaguchi, Takeshi; Nakano, Ryuichi; Yano, Hisakazu; Kasahara, Kei; Mikasa, Keiichi
Abstract: Cunninghamella is a member of the class Zygomycetes. Cunninghamella species include ubiquitous filamentous fungi; infections caused by Cunninghamella species are less frequent but have higher mortality rates than infections caused by Mucorales group members such as Rhizopus and Mucor . Herein, we reported a rare fatal case of endobronchial metastasis from breast cancer accompanied with Cunninghamella bertholletiae tracheobronchial mycetoma. A 73-year-old female with a history of right-sided breast cancer who had undergone mastectomy 11 years previously and had no recurrence presented to our emergency department with a 1-week history of left-sided back pain. Chest X-ray revealed left lung atelectasis; bronchoscopy revealed an endobronchial mass lesion in the left main bronchus. Pathological examination revealed fungal mycetoma but malignant lesions were not detected. Endobronchial and lung mycetoma caused by Cunninghamella bertholletiae were initially diagnosed; liposomal amphotericin B was administered, but her condition deteriorated. Rigid endoscopy showed growth of hemorrhagic tissue occupying the left main bronchus just under the carina. Pathological examination of the shaved lesion revealed metastasis from breast cancer covered with abundant necrotic tissue. No mold was observed in the necrotic tissue; this was probably due to liposomal amphotericin B treatment. To our knowledge, this is the first case of endobronchial metastasis from breast cancer accompanied with Cunninghamella bertholletiae mycetoma. Distinguishing endobronchial metastases from breast cancer and atypical presentations of Cunninghamella endobronchial mycetomas can be very difficult. Repeated bronchoscopies maybe helpful in establishing an accurate diagnosis when clinical prognosis does not match the initial diagnosis.